Exploring the role of nursing in addressing social determinants of health - Rani, Bhavna; Srivastava, Saumya P.; Thakur, Shefali (International Journal Of Community Medicine And Public Health, 2023)
Social determinants of health (SDOH) significantly shape an individual's well-being and health outcomes. These factors include education, income, housing, food security, and social support. There is growing recognition of the impact of SDOH on health inequities, particularly among marginalized populations. Nursing has a role in addressing these social determinants and promoting health equity. By working with community organizations and resources, nurse informaticists, nurse leaders and educators can support patients in accessing appropriate services and resources. Addressing SDOH is crucial for achieving health equity and improving overall population health. Nurses, with their holistic approach to patient care and the unique opportunity to build relationships with patients, play a critical role in addressing SDOH. By prioritizing SDOH in their practice and collaborating with interdisciplinary team members, nurses can reduce health inequities and promote optimal health outcomes for all individuals. It is essential for nurses, nurse informaticists, nurse leaders and nurse educators to actively engage in initiatives that integrate SDOH into healthcare systems and advocate for policies that address the social factors affecting health.